Assessing the vulnerability of socio-environmental systems to climate change along an altitude gradient in the Indian Himalayas. (November 2019) - Gupta, Ajay K.; Negi, Mridula; Nandy, Subrata; Alatalo, Juha M.; Singh, Vishal; Pandey, Rajiv
Highlights: Socio-Environmental Vulnerability Index (SEVI) is proposed. Weigtage allocation by Principle Component Analysis (PCA) using factor loadings and variation explained. Middle altitude zone was most vulnerable. Differential adaption strategies for different altitude. Abstract: Climate change is affecting biotic and abiotic components of the Himalayan ecosystem, disturbing existing socio-ecological systems. Future changes in the climate, coupled with ongoing development activities in the Himalayas, are likely to have a negative effect on socio-ecological systems and increase the vulnerability of the region. This study explored the socio-environmental vulnerability of socio-ecological systems at different altitudes in the Indian Himalayas. Indicators of different dimensions of vulnerability (adaptive capacity, exposure, sensitivity) were identified based on literature lists of contributing indicators. Data on the indicators were then collected in a questionnaire-based survey of 128 randomly selected households in four different altitude zones (<1000 (low), 1001–1500 (Middle), 1501–2000 (High), >2000 m a.s.l. (Very High)). Other indices were developed under the different components and significantly contributing components of these were shortlisted based on principal component analysis (PCA). The results indicated that communities in the middle and high altitude zones (1001–1500 and 1501–2000 m) were more vulnerable (score 0.68 and 0.71, respectively) than those at lower (0.42) and very high altitudes (0.49). This was probably due to high exposure to extreme events that can affect agricultural production negatively, in combination with high population density in mid-altitude communities. In contrast, there was low pressure on resources and more fertile land above 2000 m a.s.l., contributing to lower vulnerability. This analysis demonstrates that policy perspectives should not be similar across the altitude gradient in the Indian Himalayas, but should rather be formulated based on available resources, pressure, and livelihood options for achieving sustainability under climate change.